Potential Involvement of Snail Members in Neuronal Survival and Astrocytic Migration during the Gecko Spinal Cord Regeneration - Shen, Tingting; Wang, Yingjie; Zhang, Qing; Bai, Xue; Wei, Sumei; Zhang, Xuejie; Wang, Wenjuan; Yuan, Ying; Liu, Yan; Liu, Mei; Gu, Xiaosong; Wang, Yongjun (Frontiers in Cellular Neuroscience, 2017)
Certain regenerative vertebrates such as fish, amphibians and reptiles are capable of regenerating spinal cord after injury. Most neurons of spinal cord will survive from the injury and regrow axons to repair circuits with an absence of glial scar formation. However, the underlying mechanisms of neuronal anti-apoptosis and glia-related responses have not been fully clarified during the regenerative process. Gecko has becoming an inspiring model to address spinal cord regeneration in amniotes. In the present study, we investigated the regulatory roles of Snail family members, the important transcriptional factors involved in both triggering of the cell migration and cell survival, during the spontaneous spinal cord regeneration. Both Snail1 and Snail3 have been shown to promote neuronal survival and astrocytic migration via anti-apoptotic and GTPases signaling following gecko tail amputation. Transforming growth factor-beta (TGFβ), together with other cytokines were involved in inducing expression of Snail protein. Our data indicate a conserved function of Snail proteins in embryonic development and tissue regeneration, which may provide clues for CNS repair in the mammals.